Concurrent randomized control trials of the 1‐year efficacy of two couple relationship education programs: ELEVATE and Couples Connecting Mindfully. Issue 3 (19th January 2022) - Adler‐Baeder, Francesca; McGill, Julianne; Dede Yildirim, Elif; Gregson, Kimberly; Cooper, Erin; Burke, Leah; Finnegan, Vanessa; Jackel, Roberta
Abstract: A long‐standing university‐community partnership used a longitudinal randomized control trial to implement and evaluate two couple relationship education (CRE) curricula, ELEVATE and Couples Connecting Mindfully (CCM), among an economically and racially diverse population of adult couples. Married and non‐married couples ( n  = 929 couples) completed baseline surveys and were randomly assigned to either one of the two program groups or to the control group by implementation site. Follow‐up surveys were collected at 2 months, 6 months, and 1 year after baseline. Using an intent‐to‐treat approach, growth curve modeling comparisons of trajectories indicated program effects at 1 year post‐baseline in key outcome areas. Both the ELEVATE and the CCM group reported significant gains in couple relationship skills, couple quality, and family harmony over time compared to the control group that experienced either no change or declines. Further, the ELEVATE group also demonstrated positive program effects on measures of mental health and sleep quality. An assessment of the central premise of CRE indicated that the immediate post‐program improvements in couple relationship skills predicted later couple quality for both program groups. This study indicates that both ELEVATE and CCM can be considered evidence‐based CRE programs for use with a broad population of couples. Resumen: Una asociación duradera entre la universidad y la comunidad utilizó un ensayo controlado aleatorizado y longitudinal para implementar y evaluar dos currículos de educación sobre las relaciones de pareja, ELEVATE y Couples Connecting Mindfully (CCM), entre una población de parejas adultas económicamente y racialmente diversa. Parejas casadas y no casadas ( n = 929 parejas) contestaron encuestas en el momento basal, y luego, en el lugar de implementación, se las distribuyó aleatoriamente a alguno de los dos grupos del programa o al grupo de referencia. Se recogieron encuestas de seguimiento dos meses, seis meses y un año después del momento basal. Utilizando un método por intención de tratar, las comparaciones de trayectorias del modelo de curva del crecimiento indicaron efectos del programa un año después del momento basal en áreas de resultado claves. Tanto el grupo de ELEVATE como el de CCM informaron beneficios significativos en las habilidades para las relaciones de pareja, la calidad de la pareja y la armonía familiar con el tiempo en comparación con el grupo de referencia, que no tuvo ningún cambio ni empeoramientos. Además, el grupo de ELEVATE también demostró efectos del programa en las medidas de salud mental y calidad del sueño. Una evaluación de la premisa fundamental de la educación sobre las relaciones de pareja indicó que las mejoras inmediatas después del programa en las habilidades para las relaciones de pareja predijeron una posterior calidad de la pareja para ambos grupos del programa. Este estudio indica que tanto ELEVATE como CCM pueden considerarse programas factuales de educación sobre las relaciones de pareja aptos para su uso con una amplia población de parejas. 摘要: 一个存续较久的大学‐社区伙伴关系使用纵向随机对照试验(RCT)，在经济情况多样化和种族多样化的成年伴侣群体中实施和评估两门伴侣关系教育(CRE)课程，ELEVATE和伴侣有意识连接(CCM)。已婚和未婚夫妇(n = 929对夫妇)完成基线调查，并根据实施地点被随机分配到两个方案组中的任何一个或控制组。随访调查分别在基线后2个月、6个月和1年进行。使用刻意治疗方法，生长曲线建模比较轨迹表明项目在关键结果区域基线后一年的效果。随着时间的推移，ELEVATE组和CCM组在夫妻关系技巧、夫妻质量和家庭和谐方面都有显著提高，而对照组要么没有变化，要么下降。此外，ELEVATE小组还证明了方案对心理健康和睡眠质量等因素的影响。对CRE中心前提的评估表明，项目后伴侣关系技能的立即改善预示着两个项目组以后的伴侣质量。这项研究表明，ELEVATE和CCM都可以被视为基于证据的CRE项目，用于广泛伴侣群体。